Autonomic Blockade Reverses Endothelial Dysfunction in Obesity-Associated Hypertension. Issue 4 (October 2016) - Gamboa, Alfredo; Figueroa, Rocío; Paranjape, Sachin Y.; Farley, Ginnie; Diedrich, Andre; Biaggioni, Italo
Abstract : Impaired nitric oxide (NO) vasodilation (endothelial dysfunction) is associated with obesity and thought to be a factor in the development of hypertension. We previously found that NO synthesis inhibition had similar pressor effects in obese hypertensives compared with healthy control during autonomic blockade, suggesting that impaired NO vasodilation is secondary to sympathetic activation. We tested this hypothesis by determining the effect of autonomic blockade (trimethaphan 4 mg/min IV) on NO-mediated vasodilation (increase in forearm blood flow to intrabrachial acetylcholine) compared with endothelial-independent vasodilation (intrabrachial sodium nitroprusside) in obese hypertensive subjects (30<body mass index<40 kg/m 2 ). Acetylcholine and sodium nitroprusside were given at equipotent doses (10, 30, and 50 μg/min and 1, 2, and 3 μg/min, respectively) to 14 obese subjects (49±3.6 years, 34±1 kg/m 2, 165/94±7/6 mm Hg), on separate occasions 1 month apart, randomly assigned. Autonomic blockade increased basal forearm blood flow (from 3.9±0.7 to 5.2±1.2 mL/100 mL per minute, P =0.078). As expected, NO-mediated vasodilation was blunted on the intact day compared with NO-independent vasodilation; forearm blood flow increased from 3.6±0.6 to 10.1±1.1 with the highest dose of nitroprusside, but only from 3.7±0.4 to 7.2±0.8 mL/100 mL per minute with the highest dose of acetylcholine, P <0.05. In contrast, forearm blood flow responses to acetylcholine were restored by autonomic blockade and were no longer different to nitroprusside (from 6.2±1.1 to 11.4±1.6 mL/100 mL per minute and from 5.2±0.9 to 12.5±0.9, respectively, P =0.58). Our results support the concept that sympathetic activation contributes to the impairment in NO-mediated vasodilation seen in obesity-associated hypertension and provides further rationale to explore it as a therapeutic target.